Tradisi “BASOKEK” dalam Perspektif Ekonomi Islam: Studi Kasus pada Pembagian Zakat Pertanian di Jorong Supanjang Tanah Datar - Asri Tesi Ramadhani; Rizal Fahlefi; Ahmad Lutfi (Studia Economica : Jurnal Ekonomi Islam, 2025)
This study aims to analyze the meaning, value, and relevance of Basokek in the context of contemporary Islamic economic distribution. A The Basokek tradition of distributing zakat from agricultural produce in Jorong Supanjang is a form of integration between Minangkabau traditional values and Islamic economic principles. Using a qualitative approach with a case study method and interactive analysis by Miles & Huberman, data were collected through in-depth interviews with four key informants, field observations, and documentation. The results show that Basokek reflects the implementation of the principles of distributive justice (al-‘adl), trustworthiness (al-amanah), gratitude (assyukr), and mutual assistance (ta'awun) which are rooted in the teachings of the Qur'an and Sunnah. This tradition also represents the implementation of maqashid sharia, especially in safeguarding wealth (hifz al-mal) and social life (hifz al-nafs). In a modern context, Basokek has the potential to become a model for community-based zakat distribution that aligns with local values and the formal zakat institutional system. This research confirms that Islamic economics is not only embedded in the formal system but is also deeply rooted in the culture and spirituality of Muslim communities. The implication is that the baseokek tradition can provide benefits to the surrounding community, such as strengthening the community's economic resilience and has the potential to be widely adopted as a basis for reformulating national zakat distribution in a modern contectnces